Honeybee propolis extract in periodontal treatment: A clinical and microbiological study of propolis in periodontal treatment - Amita Coutinho (Wolters Kluwer Medknow Publications, 2012)
Objective: This study was conducted to evaluate by clinical and microbiological parameters the effect of subgingival irrigation with propolis extract. Materials and Methods: Twenty patients diagnosed with chronic periodontitis, each presenting three non-adjacent teeth with deep pockets, were selected. Subgingival plaque sampling and clinical recording (at baseline) and scaling and root planing was performed. Two weeks later the selected periodontal sites were submitted to one of the following treatments: Irrigation with a hydroalcoholic solution of propolis extract twice a week for 2 weeks (group A); irrigation with a placebo twice a week for 2 weeks (group B); or no additional treatment (group C). Clinical and microbiological data was collected at baseline and after 4, 6, and 8 weeks. Results: A decrease in the total viable counts of anaerobic bacteria (P=.007), an increase in the proportion of sites with low levels (≤10 5 cfu/mL) of Porphyromonas gingivalis (P=.044), and an increase in the number of sites negative for bleeding on probing was observed in group A sites as compared to group B and C sites. Conclusion: Subgingival irrigation with propolis extract as an adjuvant to periodontal treatment was more effective than scaling and root planing as assessed by clinical and microbiological parameters.